An Enhanced Framework For Automatic Voice Pathology Monitoring Based On Hidden Markov Model - et. al., Dr. K. Mohana Prasad, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Clinical analysis of voice issue and assessment of treatment result vigorously depend on exact measurement of voice quality, which is intently attached to the physiology and capacity of the laryngeal instrument. Considering the assessment strategy of the voice, two principle classes of sound-related perceptual appraisal and acoustic examination can be recognized. This work exhibits another methodology for acoustic examination of voice quality, which carries a few focal points to the field. The proposed approach is nonparametric as in it doesn't require the estimation of the principal recurrence or unearthly reaction of the vocal tract. This lessens the computational multifaceted nature of the estimation and decreases the potential blunders because of wrong estimation of those parameters. Also, the technique doesn't make any presumption about the phonetic setting and subsequently can possibly be applied to associated discourse. This work focuses on building up an exact and hearty component extraction for recognizing and grouping voice pathologies by researching diverse recurrence groups utilizing autocorrelation and entropy. We extricated greatest pinnacle esteems and their relating slack qualities from each casing of a voiced sign by utilizing autocorrelation as highlights to identify and group neurotic examples. These highlights were researched in particular recurrence groups to survey the commitment of each band to the identification and arrangement forms.